(untitled) (Journal of the College of Basic Education, 2022)
The current research is summarized by dealing with the issue of material and intellectual conditions imposed by the contemporary consumer, and this falls into the category of interactive design with the user, who has the aesthetic intellectual impact on design in general and typographic design in particular, by using the application of that through the various means and the available possibilities of ways to enrich the design action and responses intellectual receiver,